Women’s Rights in Afghanistan: From Muslims’ Perspective - Afghan, Omid (American International Journal of Social Science Research, 2019)
Considering the logic of evolution of societies, the calamitous situation of women can be both changed and controlled. With the emergence of Islam, issue of women was more deeply raised in religious and intellectual discussions. At a time when having a daughter considered a shame on Arab families, a religion emerged after which assigned key social, political and even economic rights for women. Holy Quran says there is no superiority of nations over nations, races over races and men over women unless by divine piety and good action. One of the emphatic rules of Islam is that acquiring knowledge is an obligatory act for both men and women. On the issue of education secondary data shows that most people believe Islam and Shari’a not only emphasize that girls and women should acquire Islamic education (98%), but they allow women and girls to study all levels of formal educational system. Unfortunately said, in Afghanistan, more women are scarified by men’s decisions.